Menguasai Teknik Dasar Pukulan Forehand dalam Tenis Lapangan : Tips dan Latihan Terbaik - Farhan Yazid Zidane Tanjung; Amanta Peratama Karo Karo; Redemtus Simbolon; Cyta Ibnu Aulia; Angelita Batubara; Nurkadri Nurkadri (Departement of Mathematics Education, 2023)
This article aims to provide a comprehensive guide for tennis players, especially those looking to improve their fundamental forehand stroke technique. We explore effective training methods and offer practical tips to master a powerful and consistent forehand stroke. To achieve this objective, we conducted a review of various training methods and techniques utilized by professional tennis players and renowned coaches. We also gathered knowledge from reputable sources, including tennis books and instructional videos. The results of this article consist of a comprehensive set of tips and proven exercises designed to help tennis players enhance their basic forehand stroke technique. By following the guidelines presented in this article, players will gain a better understanding of proper body movement, hand-eye coordination, and how to produce powerful and consistent forehand strokes. Through regular practice in accordance with these guidelines, players can improve their performance on the tennis court.